A spirituality for the long haul: Response to chronic illness - Muldoon, Maureen H. (Journal of religion and health, 1991)
This article outlines a spirituality appropriate for those whose lives are affected by chronic injury or illness. Spirituality may be defined simply as a sustained and lived-out vision of life. An emerging spirituality of the whole person in relation to self, others, society, the earth, and a divine presence that pervades all that is acknowledges: (1) the basic dignity of the person, and (2) the drive to growth, wholeness, and fullness in every person. It implies a respectful assistance toward whatever human growth is possible for the chronically ill, while summoning a caring presence that remains faithful despite limitations or impending death.